Student’s Perception of Using ChatGPT Voice to Improve Their Self-Efficacy in Speaking - Muhtadi, Nafsah; Kamaruddin, Abdul; Zamzam, Fadhilah; Mashuri, Mashuri (Universitas Pahlawan Tuanku Tambusai, 2025)
Speaking self-efficacy plays a crucial role in EFL learners’ oral performance, as it influences confidence, anxiety management, and willingness to communicate. Despite the growing integration of artificial intelligence in language learning, empirical studies exploring students’ perceptions of AI voice-based tools, particularly ChatGPT Voice, remain limited in the Indonesian EFL context, especially among English major students. This study aims to investigate English Education students’ perceptions of using ChatGPT Voice and examine how it contributes to their speaking self-efficacy. Employing a descriptive qualitative design, data were collected through preliminary observation interviews and in-depth semi-structured interviews with seventh-semester English Education students at Tadulako University. The findings reveal that ChatGPT Voice positively influences students’ speaking self-efficacy by increasing confidence, reducing speaking anxiety, improving fluency and vocabulary, and enhancing motivation and enjoyment. Despite minor technical challenges, students generally perceived the tool as supportive and effective. This study concludes that ChatGPT Voice serves as a valuable supplementary tool for fostering speaking self-efficacy in EFL contexts.